2012
DOI: 10.1016/j.jomh.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient education services and the organizational factors affecting them at teaching hospitals affiliated with Mashhad University of Medical Sciences (MUMS), 2008

Abstract: Background: Presenting educational and communicational programs for patients is considered to be one of the most significant executive roles of hospitals. Studying the status of patients' training services, identifying the barriers, and the organizational factors that affect these in the hospitals affiliated to the Mashhad University of Medical Sciences (MUMS) was the aim of this study. Method: This was a descriptive cross-sectional study. The participants were 441 patients, 200 physicians, 185 nurses, and 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 16 publications
(25 reference statements)
0
24
2
Order By: Relevance
“…3 It been shown that PE was a less important task of healthcare professionals from the nurse managers' perspective. 51 PE was improved through changes in the management style, development of educative materials, and patient education protocols. 3 Inappropriate educational facilities in hospital were one of the barriers perceived by Iranian nurses for PE.…”
Section: 51mentioning
confidence: 99%
See 1 more Smart Citation
“…3 It been shown that PE was a less important task of healthcare professionals from the nurse managers' perspective. 51 PE was improved through changes in the management style, development of educative materials, and patient education protocols. 3 Inappropriate educational facilities in hospital were one of the barriers perceived by Iranian nurses for PE.…”
Section: 51mentioning
confidence: 99%
“…40 It is known that faceto face PE time can be reduced by using paper materials and facilitate what must be transmitted to patients. 51 It is important to provide teaching materials which are easily understood and are consistent with cultural issues and social norms. 52 Allocation of specific space in every work-place setting for PE and assigning responsibility for this activity to one specialist nurse in the each ward by managers are another recommendations to improve and develop PE.…”
Section: 51mentioning
confidence: 99%
“…A 49-item draft scale, which contained statements reflecting the behaviours of nurses in determining patient education needs, assessment and planning, implementation, and evaluation and documentation, was developed by the researchers by reviewing studies that investigated the role of nurses in patient education (Akçin, 2006;Barber-Parker, 2002;Bastable, 2003;Copel, 2000;De Bruijn et al, 2007. Fidyk, Ventura, & Green, 2014Kaariainen & Kyngas, 2010;Bruccoliere, 2000;Kelo et al, 2013;Khorasani, Rassouli, Parvizy, Zagheri-Tafreshi, & Nasr-Esfahani, 2015;O'Connor, Devine, Cook, Wenk, & Curtin, 1990;Rankin & Stallings, 2001;Seyedin, Goharinezhad, Vatankhah, & Azmal, 2015;Şenyuva & Taşocak, 2007;Vafaee-Najar, Ebrahimipour, Shidfar, & Khani-Jazani, 2012;Willems, De Maesschalck, Deveugele, Derese, & De Maeseneer, 2005;Wingard, 2005) and based on the experiences of the researchers.…”
Section: Stage 1: Creation Of the Item Pool And Development Of The mentioning
confidence: 99%
“…Behavior was assumed influenced by attitude and belief [10], and further effected by education programs [11]. While patient education was involved in nursing education program, there is absence of the consensus on knowledge and process, and nurses were treated to be care provider rather than educator [12]. Furthermore, the function of education in nurses' role was still invisible [13].…”
Section: Informationmentioning
confidence: 99%